2017
DOI: 10.1002/jgf2.111
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for detection failures of chest radiography in diagnosing pneumonia

Abstract: BackgroundLittle is known about clinical factors associated with undetectable pneumonic shadows on chest radiographs (CRs) for diagnosing pneumonia in the primary care setting.MethodsA retrospective assessment of CRs was conducted to compare chest computed tomography (CT) images of patients admitted to Kesennuma City Motoyoshi Municipal Hospital who were diagnosed with pneumonia from April 2014 to June 2016.ResultsEighty‐three patients were included, and their average age was 83.8 years. Sixty‐eight patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…High-resolution computed tomography (HRCT) has been shown to detect more infiltrates than CXR in cases of CAP [87][88][89]. It has been suggested to be useful for early diagnosis and treatment of patients with a clinical diagnosis in hospital care [90]. However, the relevance of the findings on HRCT in primary care is unclear, because an infiltrate on HRCT but not on CXR does not necessarily indicate a bacterial infection requiring antibiotic treatment and thus risks overdiagnosis.…”
Section: High-resolution Computed Tomographymentioning
confidence: 99%
“…High-resolution computed tomography (HRCT) has been shown to detect more infiltrates than CXR in cases of CAP [87][88][89]. It has been suggested to be useful for early diagnosis and treatment of patients with a clinical diagnosis in hospital care [90]. However, the relevance of the findings on HRCT in primary care is unclear, because an infiltrate on HRCT but not on CXR does not necessarily indicate a bacterial infection requiring antibiotic treatment and thus risks overdiagnosis.…”
Section: High-resolution Computed Tomographymentioning
confidence: 99%
“…Several studies have demonstrated that in some patients with pneumonia, the disease can be identified on chest CT but not on CR images [1, 4, 5, 7, 10, 11]. Another study showed that in bedridden patients with pneumonia, the diagnostic accuracy of CR is low [6].…”
Section: Introductionmentioning
confidence: 99%